Analysis of the structural response and strengthening performance of prefabricated substation walls under flood loads - Han Yao; Liang Zhang; Qing Wang; Huina Han; Fengkai Han; Li Tian (Frontiers in Materials, 2023)
Introduction: The study focuses on evaluating the reliability of prefabricated perimeter walls in substations during flood events. It employs a sophisticated numerical model based on actual engineering data to assess their load-bearing capabilities. The research investigates the impact of crucial flood parameters on the structural behavior of these walls, examines the force transmission mechanisms, and suggests “W-shaped” reinforcement techniques to mitigate stress-related issues.Methods: To meet our research goals, we developed an extensive numerical model for prefabricated perimeter walls, incorporating real-world engineering data. This model enabled us to analyze critical flood parameters, such as flood depth, flow velocity, and flood erosion. Furthermore, we investigated the force transmission mechanisms within the walls and introduced “W-shaped” reinforcement strategies to improve their load-bearing capacity.Results: Our results indicate that flood depth and flow velocity have a substantial impact on the performance of prefabricated perimeter walls, while flood erosion has a minor effect. Safety concerns become prominent when flood depth exceeds 1.0 m or flow velocity surpasses 3 m per second. Analysis of force transmission mechanisms reveals greater displacements at higher water levels. Critical areas, including wall panel-column and wall panel-foundation connections, experience heightened stress levels.Discussion: Our study highlights the significant role of flood depth and flow velocity in evaluating the load-bearing capacity of prefabricated perimeter walls in substation environments. To address potential structural weaknesses, we recommend implementing “W-shaped” wall reinforcement methods, which efficiently decrease both displacement and stress. These findings carry implications for substation design and flood resilience, underscoring the importance of comprehensive flood risk management strategies to protect internal facilities during floods.